Environmental Properties of Tigris River at Al- Kut Dam in Wassit Province - J. AL-Shamy, Najat; S. AL-Sariy, Jameel; R. Nashaat, Muhanned (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The physical and chemical parameters of Tigris River water in AL- Kut City have been studied. Three stations have been chosen. . The sampling of study was made monthly and for six months from September 2014 until February 2015.The result of turbidity values showed height mean in summer 84 NTU, The decrease of turbidity was one of the positive results to the effect of AL-Kut Dam on the Tigris River after the Dam and on the total suspended solids. The electrical conductivity was 1340 µs/cm in winter that may be due to the existence of the polluted elements. The river water was fresh (0.48‰ semiebrachish) with a good aerated water and the height of the dissolved oxygen mean value has been noticed 13.1mg/L at many times. Over saturated Oxygen condition was noticed 135 mg/L but the biological demand of oxygen didn,t pass the national specifics with oscillation in some values. The result of hydrogen ion concentration values varied from 7.1 - 8.2 on the weak alkaline side. Height values of total hardness were recorded 600mg/L, Calcium and magnesium were the cause of hardness. The alkaline is caused by carbonate and bicarbonate ions.The present study result showed that the sulphates are more than other ions with average of 148.33mg/L.The phosphate passed the decisions of the surface water in average 0.0388µg/L.The nitrate were in the acceptable ranges in concentration from 0.296-1.75mg/L.